Phytase production by solid-state fermentation of groundnut oil cake by Aspergillus niger: A bioprocess optimization study for animal feedstock applications - Buddhiwant, Priyanka; Bhavsar, Kavita; Kumar, V. Ravi; Khire, Jayant M. (Preparative Biochemistry & Biotechnology, 2016)
This investigation deals with the use of agro-industrial waste, namely groundnut oil cake (GOC), for phytase production by the fungi Aspergillus niger NCIM 563. Plackett-Burman design (PBD) was used to evaluate the effect of 11 process variables and studies here showed that phytase production was significantly influenced by glucose, dextrin, distilled water, and MgSO4 center dot 7H(2)O. The use of response surface methodology (RSM) by Box-Behnken design (BBD) of experiments further enhanced the production by a remarkable 36.67-fold from the original finding of 15 IU/gds (grams of dry substrate) to 550 IU/gds. This is the highest solid-state fermentation (SSF) phytase production reported when compared to other microorganisms and in fact betters the best known by a factor of 2. Experiments carried out using dried fermented koji for phosphorus and mineral release and also thermal stability have shown the phytase to be as efficient as the liquid enzyme extract. Also, the enzyme, while exhibiting optimal activity under acidic conditions, was found to have significant activity in a broad range of pH values (1.5-6.5). The studies suggest the suitability of the koji supplemented with phytase produced in an SSF process by the "generally regarded as safe" (GRAS) microorganism A. niger as a cost-effective value-added livestock feed when compared to that obtained by submerged fermentation (SmF).